Balloon catheter dilation as the primary treatment of congenital nasolacrimal duct obstruction. Issue 2 (March 2021) - Gazit, Inbal; Pras, Eran; Or, Lior; Hartstein, Morris E
Purpose: The aim of this study is to report the outcome of balloon catheter dilation as the primary treatment of congenital nasolacrimal duct obstruction in children of all ages. Methods: A 10-year retrospective study of 148 children (270 eyes), aged 9 to 159 months (mean age: 29.6 ± 17.7 months), who previously had not undergone a nasolacrimal surgical procedure and who presented with clinical signs of nasolacrimal duct obstruction, was conducted. All children underwent balloon catheter dilation of the nasolacrimal duct. Results: Treatment success, defined as complete resolution of nasolacrimal duct obstruction symptoms present at follow-up visits at 1 week and up to 6 months after surgery, was 87% (234 of 270 eyes). Partial success was defined as occasional tearing which was acceptable to parents and present in 3% (nine eyes). Only 10% of the children underwent a second procedure due to complete failure. In a sub-analysis by age groups—under 18 months, between 18 and 36 months, and above 36 months—complete resolution rates were 85%, 93%, and 77%, and partial success rates were 3%, 3%, and 4%, respectively. There was a statistically significant difference between the age groups ( p  = .007). Conclusion: In this large cohort of patients with nasolacrimal duct obstruction, balloon catheter dilation was successful as a primary treatment for congenital nasolacrimal duct obstruction, particularly under the age of 36 months.